Omnichannel: What has been studied in small and medium-sized enterprises? - Santiago, Lucas; Vivaldini, Mauro (Retail Management Review, 2023)
Objective: The objective of this article is to systematize publications on omnichannel in small and medium-sized enterprises and identify the themes being addressed in this area, highlighting characteristics that aid in understanding what is being studied or not in this subject. Methodology/Approach: To achieve this objective, a bibliometric analysis was conducted, identifying the main articles, authors, journals, methodologies, and themes used in the published articles. Results: It was identified that there are few studies focusing on omnichannel in small and medium-sized enterprises. Noteworthy are the methodological diversities of the studies, and it was found that South Africa is the country that has published the most on this topic. Theoretical/Methodological Contributions: As a contribution, this research not only structures and organizes the vision of the research regarding studies focusing on omnichannel in small and medium-sized enterprises but also points out possible gaps that can be further explored. Relevance/Originality: The study highlights numerous research opportunities, such as the lack of studies pinpointing the difficulties in implementing omnichannel in small and medium-sized enterprises, approaches that map the service processes, and define the necessary operational structure.